Drug resistance pattern analysis of various organisms isolated from neonatal intensive care unit of a tertiary care hospital in Odisha, India - Sarangi, Kausik Kumar; Pattnaik, Dipti; Mishra, Surya Narayan; Nayak, Manas Kumar; Jena, Jagadananda (International Journal of Advances in Medicine, 2017)
Background: Neonatal septicaemia is characterized by systemic signs and symptoms of generalized bacteraemia with a positive blood culture in the first four weeks of life. This study was designed to detect Multi Drug Resistant pattern from organisms in neonatal septicaemic cases. The aim of the study is to find the antibiotic sensitivity pattern and drug resistance pattern (ESBL, MBL, Carbapenemase, AmpC β-lactamase, MRSA) among the organisms isolated. Methods: This prospective study was carried out in the Department of Microbiology in association with Dept. of Paediatrics and NICU, of Kalinga Institute of Medical Sciences, Bhubaneswar, Odisha, India during the period from November 2012 - April 2014. The study was conducted on 250 patients. The inclusion criteria are neonates with suspected septicaemia, admitted to NICU, of KIMS, Bhubaneswar, Odisha, India. Two ml of venous blood from each neonate was collected & cultured by automated method. Phenotypic confirmatory tests for ESBL production and MBL detection was done as per CLSI guideline. MRSA detection was done by Cefoxitin disk (30 mcg) screen test. Results: All gram positive pathogenic isolates were sensitive to Linezolid, Tigecycline and Vancomycin. Maximum resistance was seen against Benzylpenicilin and Ampicillin. Among the gram-negative isolates maximum antibiotic sensitivity was observed for Tigecycline, Levofloxacin and amikacin & resistance was maximum for cefadroxil and Ampicilin. Among the gram negative bacterial pathogens ESBL production was maximum by E.coli (75%) and Burkholderia cepacia (75%) followed by Enterobacter cloacae (66.7%) and Acinetobacter iwoffi (50%). Metallo- beta- lactamase production was seen maximum in Acinetobacter iwoffi (100%) followed by Burkholderia cepacia (75%). Methicillin resistance was seen maximum by S. epidermidis (58.3%) followed by S. haemolyticus, S. aereus, S. warneri and S. hominis. Conclusions: This study facilitated the screening of MRSA, ESBL and MBL producing pathogens which are an emerging problem. Long term surveillance is needed to combat this emerging global challenge.